Design and development of an autonomous surface vessel for inland water depth monitoring - Mat Idris, Mohd Hilmi; Sahalan, Mohd Irshad; Che Kamarudin, Muhammad Al Azhari; Zainal Abidin, Zulkifli; Rashid, Muhammad Mahbubur (The Institute of Electrical and Electronics Engineers, Inc., 2016)
This paper is about design and development of an Autonomous Surface Vessel (ASV) for inland water depth monitoring. Water depth measurement a.k.a bathymetry is important for critical areas such as river and water reservoir (dam) to estimate the volume and surface area for environment conservation and safety purpose. Conventionally, in inland water monitoring, the data obtained from the measurements are recorded in the log book and have to go through some screening process before plotting contour. This procedure is not only slow but also requires a lot of logistic equipment and labor forces. Therefore, an Autonomous Surface Vessel equipped with an echo sounder and data telemetry is proposed. It can be either remotely controlled or run automatically by autopilot navigation software. It is also equipped with GPS and compass for the navigation sensor feedback. The ASV was tested at several lakes for the performance of data collection and navigation.